11-Keto-β-Boswellic Acid Inhibits Lymphocyte (CD3) Infiltration Into Pancreatic Islets of Young None Obese Diabetic (NOD) Mice - Shehata, Ahmed M.; Quintanilla-Fend, Leticia; Bettio, Sabrina; Kamyabi-Moghaddam, Zahra; Kohlhofer, Ursula A.; Scherbaum, Werner A.; Ammon, Hermann P.T. (Hormone and Metabolic Research, 2017)
11-Keto-β-Boswellic acid (KBA) has been shown to prevent infiltration of lymphocytes into pancreatic islets and appearance of peri-insular apoptotic cells in an animal model of autoimmune diabetes caused by injection of Multiple Low Doses of Streptozotocin (MLD-STZ), which is a chemical compound belonging to the class of nitrososureas. The aim of this work was to study whether or not KBA can also prevent/attenuate infiltration of lymphocytes into pancreatic islets and appearance of peri-insular apoptotic cells in an animal model of autoimmune diabetes caused by genetic dysfunction resembling human type 1 diabetes in several important features. Four weeks old female NOD mice received daily i.p. injections of 7.5 mg/kg of KBA over a period of 3 weeks. Compared to 4 weeks old animals there was significant infiltration of lymphocytes (CD3) into pancreatic islets and appearance of peri-insular apoptotic cells in the period between 4 and 7 weeks. During this time plasma glucose dropped significantly and body weight did not increase. As far as pro-inflammatory cytokines are concerned, except a small increase of IFN-γ, there was no change in the blood. In mice that had been treated with KBA between 4 and 7 weeks after birth no significant infiltration of lymphocytes into pancreatic islets and appearance of peri-insular apoptotic cells was observed, when compared to 4 weeks old mice. Moreover, there was no drop of blood glucose and the animals gained body weight. It is concluded that – similar to the model of MLD-STZ-diabetes – also in the NOD mouse model KBA is able to attenuate or even prevent development of insulitis, suggesting that KBA protects islets from autoimmune reaction regardless whether the signal is provided by a chemical compound or by genetic dysfunction. Whether this also holds for human type 1 diabetes remains to be established.
Keywords: boswellic acids; NOD mice; prevention; insulitis; histochemistry; cytokines